2019
DOI: 10.1016/j.envpol.2019.04.093
|View full text |Cite
|
Sign up to set email alerts
|

Do transparent exopolymeric particles (TEP) affect the toxicity of nanoplastics on Chaetoceros neogracile?

Abstract: The potential presence of nanoplastics (NP) in aquatic environments represents a growing concern regarding their possible effects on aquatic organisms. The objective of this study was to assess the impact of polystyrene (PS) amino-modified particles (50 nm PSNH2) on the cellular and metabolic responses of the diatom Chaetoceros neogracile cultures at two essential phases of the growth cycle, i.e. exponential (division) and stationary (storage) phases. Both cultures were exposed for 4 days to low (0.05 μg mL−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 56 publications
1
47
0
2
Order By: Relevance
“…The measurement of ζ-potential (mV) by EM can be used as an indicator of the NP surface charge and, thus, colloidal stability in the medium, with low absolute values usually associated with the screening of NP surface charge (Mourdikoudis et al, 2018). DLS and EM techniques are usually coupled with scanning or transmission electron microscopy (SEM/TEM), which allow to display the agglomeration state of colloidal suspensions and also the specific interactions occurring at the biological surfaces, such as bacteria (Gupta et al, 2016;Fu et al, 2018), microalgae (e.g., Chen et al, 2011;Wang et al, 2016;Bergami et al, 2017;González-Fernández et al, 2019;Seoane et al, 2019), and invertebrate cells (e.g., Canesi et al, 2016a,b;Ciacci et al, 2019). The limit of these techniques is the high concentration of the sample required (usually in the range of µg ml −1 ) (Ribeiro et al, 2017), which often do not reflect PECs for the anthropogenic NPs, in the range of µg L −1 for TiO 2 NPs and ng L −1 for PS NPs (da Silva et al, 2011;Gottschalk et al, 2013).…”
Section: Np Fate and Behavior In Sea Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of ζ-potential (mV) by EM can be used as an indicator of the NP surface charge and, thus, colloidal stability in the medium, with low absolute values usually associated with the screening of NP surface charge (Mourdikoudis et al, 2018). DLS and EM techniques are usually coupled with scanning or transmission electron microscopy (SEM/TEM), which allow to display the agglomeration state of colloidal suspensions and also the specific interactions occurring at the biological surfaces, such as bacteria (Gupta et al, 2016;Fu et al, 2018), microalgae (e.g., Chen et al, 2011;Wang et al, 2016;Bergami et al, 2017;González-Fernández et al, 2019;Seoane et al, 2019), and invertebrate cells (e.g., Canesi et al, 2016a,b;Ciacci et al, 2019). The limit of these techniques is the high concentration of the sample required (usually in the range of µg ml −1 ) (Ribeiro et al, 2017), which often do not reflect PECs for the anthropogenic NPs, in the range of µg L −1 for TiO 2 NPs and ng L −1 for PS NPs (da Silva et al, 2011;Gottschalk et al, 2013).…”
Section: Np Fate and Behavior In Sea Watermentioning
confidence: 99%
“…Studies on PS NPs and phytoplankton have usually been performed following available standardized toxicity test protocols to determine the growth inhibition at 72 or 96 h of an algal culture in an exponential phase exposed to a contaminant (e.g., ISO, 2006;OECD 201, 2011). Interestingly, most of the studies reported no or limited effect on microalgal growth after exposure to increasing concentrations of plain PS and PS-COOH NPs (Bergami et al, 2017;Yi et al, 2019) up to 250 µg ml −1 (Sjollema et al, 2016), while many sub-lethal physiological alterations have been observed, such as a strong adsorption of nanoplastic agglomerates on microalgal surface (Bergami et al, 2017;Sendra et al, 2019b;Yi et al, 2019), a decrease in photosynthesis efficiency and lipid content, as well as the production of reactive oxygen species (ROS) (González-Fernández et al, 2019;Sendra et al, 2019b;Seoane et al, 2019). Moreover, a significant increase in the DNA damage as well as depolarization of mitochondrial and cell membrane were found in the benthic diatom Phaeodactylum tricornutum exposed to increasing concentrations (in the range 0.1-50 µg ml −1 ) of plain PS NPs, although toxicity was not affected by their nominal sizes of 50 and 100 nm (Sendra et al, 2019b).…”
Section: Effects On Marine Organismsmentioning
confidence: 99%
“…When cell concentrations at T f were not significantly different between controls and copepod tanks, grazing was considered under the detection limit (i.e., <dl in Table 4). Ingestion rates were converted to ng Chl a ind −1 d −1 using a literature-based mean value of 0.10 pg Chl a cell −1 for S. marinoi (Norici et al, 2011;Chandrasekaran et al, 2014;Orefice et al, 2016;Smerilli et al, 2019) and 0.35 pg Chl a cell −1 for C. neogracile (unpublished data from González-Fernández et al, 2019).…”
Section: Specific Growth Rate and Grazing Parametersmentioning
confidence: 99%
“…Cell variables—i.e., forward scatter (forward scatter, FSC), side scatter (side scatter, SSC), and red fluorescence (FL3, red emission filter long pass, 670 nm, a proxy of chlorophyll content)—were used to identify and select the A. minutum cell population. FSC and SSC give, respectively, information on the relative size and complexity of cells [ 62 , 63 , 64 ]. The flow cytometry measurements were performed on fresh (live) samples.…”
Section: Methodsmentioning
confidence: 99%